THE EFFECT OF SCAVENGER HUNT GAME TOWARDS STUDENTS' VOCABULARY MASTERY OF THE FOURTH GRADE AT SDN 4 MUARA BELITI - Endar Pradesta (Lingustic, Literature and English Education, 2026)
This study aims to assess the completeness of learning outcomes related to the effectiveness of the Scavenger Hunt Game method in enhancing students' vocabulary skills at SDN 4 Muara Beliti. A pre-experimental approach was employed, utilizing a one-group pre-test and post-test design, with a sample of 20 fourth-grade students. The sampling technique adopted was purposive sampling. The analysis technique used a normality test, while the hypothesis was tested with a paired sample t-test. The pre-test showed an average score of 41.50 with a standard deviation of 17.021, with only 2 students reaching the "Mastered" level. After four treatment sessions using the Scavenger Hunt Game, the post-test average increased to 74.75 with a standard deviation of 10,818, and 12 students achieved the "Mastered" qualification. The results of these tests indicated that the paired sample t-test yielded a significant value lower than 0.05 (0.001 < 0.05). This means that Ha, which stated that there is a significant difference in students’ vocabulary mastery before and after being taught using the scavenger hunt game for the fourth graders at SDN 4 Muara Beliti, was accepted. Meanwhile, H0, which stated that there is no significant difference in students’ vocabulary mastery before and after being taught using the scavenger hunt game for the fourth graders at SDN 4 Muara Beliti, was rejected. In conclusion, the scavenger hunt game can be used as an alternative method to teach vocabulary to elementary school students.